2013
DOI: 10.1210/jc.2013-1006
|View full text |Cite
|
Sign up to set email alerts
|

Hip Structural Analysis in Adolescent and Young Adult Oligoamenorrheic and Eumenorrheic Athletes and Nonathletes

Abstract: In an eugonadal state, athletic activity confers benefits for hip structure independent of aBMD. This advantage is lost in AAs, who do not differ from nonathletes for most parameters and fare worse than EAs for cross-sectional area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…Studies to date, however, have failed to definitively determine the impact of menstrual cycle disturbances among athletes on femoral neck geometry. Duckham et al [7] and Ackerman et al [6] reported smaller femoral neck CSA among amenorrheic athletes compared with eumenorrheic athletes when categorized according to current self-reported menstrual status. However, similar to the findings presented herein, we previously reported no difference in femoral neck CSA and CSMI between amenorrheic and eumenorrheic exercising women who were categorized according to current menstrual status [12].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies to date, however, have failed to definitively determine the impact of menstrual cycle disturbances among athletes on femoral neck geometry. Duckham et al [7] and Ackerman et al [6] reported smaller femoral neck CSA among amenorrheic athletes compared with eumenorrheic athletes when categorized according to current self-reported menstrual status. However, similar to the findings presented herein, we previously reported no difference in femoral neck CSA and CSMI between amenorrheic and eumenorrheic exercising women who were categorized according to current menstrual status [12].…”
Section: Discussionmentioning
confidence: 98%
“…Historically, the majority of studies focusing on the effects of menstrual cycle disturbances have naturally focused on BMD, the bone health variable clinically used to diagnose osteoporosis. However, with technological advances in bone health imaging, such as HSA, and greater accessibility to other modes of bone imaging, such as QCT, there has been an additional focus on bone geometry among female athletes with menstrual disturbances [5][6][7]12,27,50]. These advancements in the field of women's bone health are important due to the major influence that bone geometry has on overall bone health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations